2021
DOI: 10.1186/s12889-021-10892-9
|View full text |Cite
|
Sign up to set email alerts
|

Caregiver burden and parenting stress among left-behind elderly individuals in rural China: a cross-sectional study

Abstract: Background One public health problem that cannot be ignored is the mental health of left-behind elderly individuals in rural areas. However, the burden of care and parenting stress among left-behind elderly individuals has never been analyzed. The purpose of this study was to explore the level of caregiver burden and parenting stress and their relationship among left-behind elderly individuals. Methods A total of 261 left-behind elderly people resp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 28 publications
2
6
0
Order By: Relevance
“…In line with previous reports on gender differences in the experience of caregiving for a family member (Pinquart & S örensen, 2006) and raising grandchildren (Park, 2009;Zhao et al, 2021), women in this study reported greater subjective stress. In addition, the results indicate that greater perceived overload was associated with greater depressive symptoms among women than men, in support of previous studies (e.g., Zhao et al, 2021).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In line with previous reports on gender differences in the experience of caregiving for a family member (Pinquart & S örensen, 2006) and raising grandchildren (Park, 2009;Zhao et al, 2021), women in this study reported greater subjective stress. In addition, the results indicate that greater perceived overload was associated with greater depressive symptoms among women than men, in support of previous studies (e.g., Zhao et al, 2021).…”
Section: Discussionsupporting
confidence: 91%
“…In line with previous reports on gender differences in the experience of caregiving for a family member (Pinquart & S örensen, 2006) and raising grandchildren (Park, 2009;Zhao et al, 2021), women in this study reported greater subjective stress. In addition, the results indicate that greater perceived overload was associated with greater depressive symptoms among women than men, in support of previous studies (e.g., Zhao et al, 2021). The experience of higher subjective stress and depressive symptoms may be related to the common view of women as expected caregivers and the propensity of women to take nurturing roles and assume major responsibility for the care of others, even if they exceed their personal resources (Bullock, 2005).…”
Section: Discussionsupporting
confidence: 91%
“…However, determining whether the elderly will have children capable of providing for them is difficult [ 36 ]. With the development of the economy and society over the past 30 years, the number of left-behind elderly people has increased rapidly in rural China and other countries [ 37 ]. These elderly people have increased DPD risk with regard to physical, mental, social, and economic areas; however, a study showed that only an extremely small proportion of elderly people are physically dependent [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…A score of <21 indicates no burden or a mild burden, a score of 21–39 indicates a moderate burden, and a score of ≥40 indicates a severe burden on each scale, which includes five grades from 0 (none) to 4 (always) ( 39 ). The Chinese version of the ZBI has good reliability and validity for caregiver burden surveys, and the Cronbach’s coefficient of the scale is 0.86 ( 40 ).…”
Section: Methodsmentioning
confidence: 99%